Medical negligence disputes in Malaysia: resolving through hazards of litigation or through community responsibilities? - Jahn Kassim, Puteri Nemie; Mohd Najid, Khadijah (World Academy of Science, Engineering and Technology (W A S E T), 2013)
Medical negligence disputes in Malaysia are mainly resolved through litigation by using the tort system. The tort system,being adversarial in nature has subjected parties to litigation hazards such as delay, excessive costs and uncertainty of outcome. The dissatisfaction of the tort system in compensating medically injured victims has created various alternatives to litigation. Amongst them is the implementation of a no-fault compensation system which would allow compensation to be given without the need of proving fault on the medical personnel. Instead, the community now bears the burden of compensating and at the end, promotes collective responsibility. For Malaysia, introducing a no-fault system would provide a tempting solution and may ultimately, achieve justice for the medical injured victims. Nevertheless, such drastic change requires a great deal of consideration to determine the suitability of the system and whether or not it will eventually cater for the needs of the Malaysian population.